Adolescent Athletes Demonstrate Inferior Objective Profiles at the Time of Return to Sport After ACLR Compared With Healthy Controls. Issue 1 (12th January 2022) - Robinson, John D.; Hannon, Joseph; Goto, Shiho; Singleton, Steven B.; Garrison, J. Craig
Background: Athletes display persistent muscle deficits and altered limb-loading mechanics at the time of return to sport (RTS) after anterior cruciate ligament reconstruction (ACLR). Purpose: To compare an objective profile of adolescent athletes at RTS after ACLR to matched healthy controls. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Included were 124 participants; 62 patients who underwent ACLR (15.4 ± 1.7 years) and 62 healthy controls (15.3 ± 1.7 years). Motion capture and force plates were used to capture joint motions during jump landing (JL) and single-limb squat (SLS) tasks. Energy absorption contribution (EAC) was calculated, and repeated-measures analysis of variance was used to assess for EAC differences between groups. Participants completed an International Knee Documentation Committee (IKDC) Subjective Knee Form, and isokinetic quadriceps and hamstring strength testing was performed on each limb. Independent t tests were run to examine age, height, weight, and IKDC scores as well as compare differences between groups for quadriceps and hamstring strength. Results: A significant group × joint interaction was found for JL ( P < .001) and SLS ( P < .001). For JL, patients who underwent ACLR utilized significantly greater hip ( P < .001) and significantly less knee ( P < .001) EAC on the surgical limb compared with controls. During SLS, patients who underwent ACLR utilized significantly greater hip ( P < .001) and significantly less knee ( P < .001) EAC on the surgical limb compared with controls. The ACLR cohort demonstrated lower IKDC scores ( P < .001) and significantly lower quadriceps strength on the surgical limb ( P < .001) than controls. There were no differences in surgical limb hamstring strength between the ACLR cohort and healthy controls ( P = .701). Conclusion: Compared with matched healthy controls, the participants who underwent ACLR in this study demonstrated an inferior objective profile at RTS, consisting of deficits in surgical limb loading, self-reported outcomes, and strength.